ANALISA PEMANFAATAN TEKNOLOGI, CUSTOMER DELIVERED VALUE FITUR PELAYANAN, CITRA MEREK, DAN PERILAKU KONSUMEN PADA MASA PANDEMI COVID-19 TERHADAP KEPUASAN KONSUMEN GRAB DI KOTA BATAM - Sapuan, Sapuan; Samad, Samad (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
From the results of the study the authors concluded that partially count (X1) has a positive and significant effect on customer satisfaction, with a t value of 9.641 with a significant level of 0.000. Customer deliverd value (X2) has a positive and significant effect on customer satisfaction with a t value of 12.281 with a significant level of 0.000. Brand image (X4) has a positive and significant effect on customer satisfaction with a t value of 2.226 with a significant level of 0.029. Consumer behavior (X5) has a positive and insignificant effect on customer satisfaction with a t value of 8.645 with a significant level of 0.000. Judging from the simultaneous or joint test that knowing the effect of technology use (X1), customer delivered value (X2), service features (X3), brand image (X4), and consumer behavior (X5) simultaneously have a positive and significant effect on Consumer satisfaction variable (Y) with a value that f counted at 496.822 and significant with a significant value of 0.000.